(untitled) (Comprehensive Journal of Science, 2025)
The study of citrus crops and the identification of their characteristics is considered one of the important fields of research for humanity across different regions of the world throughout various historical periods. The aim of this research is to identify the impact of climate on citrus crops, to examine the suitability of climatic conditions for increasing their productivity, and to determine the types of pests that affect the fruits. The study adopted the descriptive–analytical approach to describe the areas where different types of citrus trees are widely cultivated, as well as the comparative approach to compare different regions within the study area. The study reached several findings, most notably that climate has a significant effect on citrus production, whether by increasing or decreasing it. A decline in rainfall combined with rising temperatures led to a reduction in production levels and the death of many trees. In addition, the decrease in groundwater reserves in the study area and the high level of soil salinity had a considerable negative impact on productivity as well.